Application of Burhani Reasoning by Abid Al-Jabiri in Developing MI Curriculum - Hasan, Moh Ferdi; Arifi, Ahmad; Rina Hardiyana, Minati (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
This research examines the implementation of the concept of Burhani reasoning by Abid al-Jabiri in the curriculum development of Madrasah Ibtidaiyah (MI) School. Through a qualitative approach and case study method, this research explores how Burhani reasoning has been successfully applied by teachers, principals, and students in MI. Data collection techniques through in-depth interviews, participatory observation, and curriculum documentation study. The research results show that Burhani reasoning has been successfully applied in the MI curriculum and the integration of teaching methods based on Burhani reasoning with traditional methods has been successful. This has an impact on increasing students' critical and logical thinking abilities. This study suggests the importance of continuous training for teachers in applying Burhani reasoning in teaching and suggests further research to see the long-term impact of the implementation of Burhani reasoning on student learning outcomes. In conclusion, the application of Burhani reasoning has been proven to improve the quality of education in MI.